Brain circuits involved in understanding our own and other’s internal states in the context of romantic relationships - Esménio, Sofia (2019)
Social interactions require the capacity to understand both our and other’s internal states. These semi-independent skills, the ability to understand oneself and others, seem to rely on the same type of representations and recruit similar brain areas. In this study, we looked at the neural basis of self and other processing in the context of an interaction with a significant other. Fourty-two participants in a monogamous relationship completed an fMRI task in which they watched a set of video-vignettes of his/her romantic partner expressing emotional contents. Participants were asked to elaborate on his/her spouse´s experience (other condition) and on his/her own experience when watching the video-vignettes (self-condition). The results showed a significant overlap in the brain activation for both conditions (e.g. anterior insula, posterior cingulate/precuneus, inferior frontal gyrus, inferior parietal lobule). In addition, the self-condition recruited brain areas associated with interoceptive processing and affect sharing (e.g., posterior insula), whereas the other-condition engaged brain areas involved in the cognitive representation of another’s internal states and self-other distinction (e.g., fusiform, supramarginal gyrus, angular gyrus and temporoparietal junction).